Fenomenologia e consciência-tempo [Zeitbewusstsein] : a dupla intencionalidade e a unidade da consciência absoluta nas análises de Husserl - Isabela Carolina Carneiro de Oliveira (2023)
The present research presents an initial investigation on phenomenological temporality in Edmund Husserl. To do so, we first explain the Husserlian's critique of the origin of time in Brentano. Considering time as the founding element of his phenomenological analyses, we emphasize the sovereignty and unity of absolute consciousness, as it ensures the distinction between acts of perception, remembrance, expectations of the future and fantasy in the simultaneity in which these experiences [Erlebnisse] are unified by internal consciousness. In this context, we elucidate the necessary relationship between transversal and longitudinal intentionality, since this interweaving makes it possible to understand the unity of consciousness in the correspondence and adequacy between the transversal intentionality in the flow phases and the longitudinal intentionality that constitutes immanent time. From this, we examine the phenomenological specificity of each phase of the flow of consciousness: primal impression, retention and protention, as well as the continuity of the constitutive flow of time. Among the phases of the flow, the protentional was resignified by Husserl in his intermediate texts on phenomenological temporality, for this reason, we direct attention to the function of protention within retention and retention within protention. As retention and protention are passive syntheses of consciousness, we resume some of the clarifications given by Husserl on passive genesis with the intention of elucidating the importance of affective awakening in the living present and the need for associative syntheses that presuppose and are founded on temporal syntheses. Finally, we thematized the function of sensitive contents, because a report on temporal syntheses would remain incomplete if it did not explain the connections at the level of hyletic data with intentional experiences.